2023
DOI: 10.1002/jso.27268
|View full text |Cite
|
Sign up to set email alerts
|

Comparing carbon nanoparticles and indocyanine green for sentinel lymph node mapping in endometrial cancer: A randomized‐controlled single‐center trial

Abstract: Background and Objectives: To compare the feasibility and diagnostic value of sentinel lymph node (SLN) mapping with carbon nanoparticles (CNPs) and indocyanine green (ICG) in endometrial cancer (EC).Methods: This was a single-center, open-label, randomized controlled trial. Between August 1, 2020 and April 30, 2022, patients with early-stage EC were assessed for enrollment. All patients underwent SLN mapping with ICG or CNPs ± pelvic and/or para-aortic lymphadenectomy. The detection rate (DR), its impact fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Moreover, ICG was found to be superior to carbon nanoparticles in lymph node tracing in thyroid cancer surgery, resulting in a higher number of lymph nodes harvested at a lower cost [47]. However, He et al found similar outcomes between ICG and carbon nanoparticles during surgery for endometrial cancer [48], pointing out that carbon nanoparticles can be used when near-infrared imaging equipment is not available. Another study by Qin et al showed that the combination of ICG and methylene blue has better results in the detection of sentinel lymph nodes in surgery for breast surgery [49].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ICG was found to be superior to carbon nanoparticles in lymph node tracing in thyroid cancer surgery, resulting in a higher number of lymph nodes harvested at a lower cost [47]. However, He et al found similar outcomes between ICG and carbon nanoparticles during surgery for endometrial cancer [48], pointing out that carbon nanoparticles can be used when near-infrared imaging equipment is not available. Another study by Qin et al showed that the combination of ICG and methylene blue has better results in the detection of sentinel lymph nodes in surgery for breast surgery [49].…”
Section: Discussionmentioning
confidence: 99%
“…ICG has been shown superior to blue dye and Tc99 combination for the detection of SLNB [ 4 , 5 ]. On the other hand, carbon dye, consisting of carbon nanoparticles with a diameter of 150 μm, enters the lymphatic circulation by macrophages and is mainly excreted through the gastrointestinal tract [ 6 ]. Carbon dye, which has a strong staining ability and high contrast capacity due to its dark black color, enables the lymph nodes efficiently identified.…”
mentioning
confidence: 99%
“…Thereafter, carbon dye has gained acceptance among general surgeons in SLNB procedures. The present study is one of the few studies using carbon dye alone as a tracer during the SLNB procedure in endometrial cancer [ 6 , 12 , 13 ]. Therefore, the objective of the present study was to evaluate the safety and efficacy of carbon dye for the detection of sentinel lymph nodes in endometrial cancer patients.…”
mentioning
confidence: 99%